2017
DOI: 10.1242/dev.157644
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB4 control of Akt signaling is essential for premigratory and migratory neural crest formation

Abstract: Neural crest (NC) specification comprises an early phase, initiating immature NC progenitors formation at neural plate stage, and a later phase at neural fold stage, resulting in a functional premigratory NC that is able to delaminate and migrate. We found that the NC gene regulatory network triggers upregulation of (6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 4) during this late specification phase. As shown in previous studies, PFKFB4 controls AKT signaling in gastrulas and glycolysis rate in adult … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…Gli1 is a transcription factor that is required for differentiation of neural crest cells [89,90], and the acetylation of Gli1 by Kat2b may be one of the potential contributors to the kat2b −/− cartilage phenotype. Another substrate of Kat2b, Akt1, has been found to be correlated to the regulation of neural crest cells specification and migration [91] and embryonic skeletal development [92], and mutated in patients with craniofacial defects, including mandible and frontal bone deformities [93]. In addition, acetylation of Akt1 by Kat2b has been shown to regulate cell proliferation and survival in vitro [61,94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Gli1 is a transcription factor that is required for differentiation of neural crest cells [89,90], and the acetylation of Gli1 by Kat2b may be one of the potential contributors to the kat2b −/− cartilage phenotype. Another substrate of Kat2b, Akt1, has been found to be correlated to the regulation of neural crest cells specification and migration [91] and embryonic skeletal development [92], and mutated in patients with craniofacial defects, including mandible and frontal bone deformities [93]. In addition, acetylation of Akt1 by Kat2b has been shown to regulate cell proliferation and survival in vitro [61,94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the importance of AKT phosphorylation and CNC migration (Bahm et al, 2017; Figueiredo et al, 2017). In particular, the Mayor group revealed that PDGFR stimulation results in increased AKT phosphorylation and N-cadherin expression, which in turn contributes to the transition from pre- to post-migratory CNC (Bahm et al, 2017).…”
Section: Phenotypical Analysismentioning
confidence: 89%
“…The neural crest also seems atypical as seen by abnormal melanocyte patterning along the body axis and malformation of the dorsal fin (Figure 5A). In tailbud stage embryos, there is a strong reduction of twist marker expression ( Figure 5B), which is specific for head/craniofacial neural crest cells (Figueiredo et al, 2017). Additionally, neural crest derived head cartilage formation is perturbed and reduced in ASXL3 morphant embryos (Figure 5C).…”
Section: Inhibition Of Asxl3 Differentially Modifies Noggin Neural Inmentioning
confidence: 99%
“…Ovulation, in vitro fertilization, culture, explant dissection and treatment were as described (Re'em-Kalma et al, 1995;Bonstein et al, 1998). Embryos were stained with Alcian Blue for cartilage detection at tadpole stages (Figueiredo et al, 2017).…”
Section: Xenopus Embryos and Explantsmentioning
confidence: 99%
See 1 more Smart Citation